Design of slip-based traction control system for EV and validation using co-simulation between Adams and Matlab/Simulink. (June 2020) - Saha, Sudipta; Amrr, Syed Muhammad
This paper focuses on controlling traction for a four-wheel electric vehicle by using the longitudinal slip ratio control technique. By keeping the slip ratio value inside an optimal limit, it can be ensured that the maximum driving force is obtainable by increasing the friction force between tire and road. The usefulness of the sliding mode control method is to provide robust performance from the parameter uncertainties at different road conditions. A control law is formulated based upon the Lyapunov stability approach to assure the sliding action. To satisfy the robustness, a vehicle model is made in Matlab, and it is simulated based on various parameter values. The slip ratios at different parameter values are plotted for open loop and closed loop. Then considering the vehicle kinematics and dynamics, a 3D CAD model using Catia is developed. Then exporting the model to Adams to use it as a plant model for the vehicle, co-simulation has been achieved by keeping the slip-based traction controller in Matlab/Simulink. Matlab/Simulink and Adams/View simulation validate the proposed method.